(untitled) (Collection of scientific works «Modern structures of metal and wood», 2022)
Metal capacities for the storage bulk materials are became widespread every year. The design of the steel spiral-fold silos and the peculiarities of the folding lock are considered in the article. The elements of the rigidity system of prefabricated metal silos from corrugated panels on bolted joints are given. The characteristics of the silo from which the samples were taken for the experiment are described. The mechanical characteristics of DX51D + Z140 steel, which were calculated by testing samples for tension, are given. Samples and equipment for experimental study of a folding lock are illustrated. The stages of the experiment are described. The samples were loaded with a central tensile load, which was applied in static mode in the range from 0 kN to 21 kN. The stages of opening the folding lock depending on the tensile load are illustrated. The stages of the folding lock’s work are described. The complete character of disclosing of the folding lock to its ruination is described. The character of the folding lock’s work in the elastic stage is analyzed. The analysis of sample’s relative strains which were measured by AVD-4 is made. It was noted that the folding rib and the adjacent shell work in a complex stressed state. The mirror strain gauges showed opposite signs, and as a result, when the folding lock is disclosing, the silo wall is compressed on one side and tensioned on the other one. The samples after the destroying of the folding connection are illustrated, it is noted that the metal was observed areas of thinning of the metal and cracks. The comparison of research results with the analytical calculations received at designing of a design of a silo is made. According to the results of calculations, it was noted that in an empty silo under the action of wind load there are not only meridional compressive stresses, but also tensile. According to the results of experimental research and comparison of the obtained data with analytical calculations, it was found that the operating loads correspond to the initial stage of the folding lock’ work. The experimentally studied design of the folding lock provides reliable work of a silo on design loadings.